2005
DOI: 10.1111/j.1365-2222.2005.02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway generation‐specific differences in the spatial distribution of immune cells and cytokines in allergen‐challenged rhesus monkeys

Abstract: SummaryBackground-Accumulation of immune cell populations and their cytokine products within tracheobronchial airways contributes to the pathogenesis of allergic asthma. It has been postulated that peripheral regions of the lung play a more significant role than proximal airways with regard to inflammatory events and airflow obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 64 publications
5
52
0
Order By: Relevance
“…It is possible that a different inflammatory milieu exists in the airways, with a gradient in cytokine expression. Using an allergen-induced asthma model in rhesus monkeys, Miller et al [27] reported increased levels of cytokines and chemokines within the distal lung, whereas CD4+ lymphocytes accumulated preferentially in the proximal to midlevel region of the lungs. The authors proposed that the distal lung may be involved in the mobilisation of effector immune cells into the airways and that the proximal airways may serve as a reservoir for immune cells that contribute to chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a different inflammatory milieu exists in the airways, with a gradient in cytokine expression. Using an allergen-induced asthma model in rhesus monkeys, Miller et al [27] reported increased levels of cytokines and chemokines within the distal lung, whereas CD4+ lymphocytes accumulated preferentially in the proximal to midlevel region of the lungs. The authors proposed that the distal lung may be involved in the mobilisation of effector immune cells into the airways and that the proximal airways may serve as a reservoir for immune cells that contribute to chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The disease is characterized by airflow obstruction that varies over time and in response to treatment 3,4 and by airway hyperresponsiveness to stimuli, such as allergens, irritants, cold air, and viruses. Histologic studies performed in patients who died during an acute asthma attack have shown that the inflammatory changes within the lungs of patients with asthma are heterogeneously distributed throughout the lungs.…”
mentioning
confidence: 99%
“…All of these cell types accumulate within airways in unique patterns of distribution, suggesting compartmentalised responses with regard to trafficking. Although cytokine mRNA levels are elevated throughout the conducting airway tree of HDMA-challenged animals, the distal airways (terminal and respiratory bronchioles) exhibit the most pronounced upregulation [73].…”
Section: Airway Physiologymentioning
confidence: 99%